Cladocera and copepoda (Crustacea) fauna of seli stream (Elazığ-Turkey) - Saler, Serap; İpek, Necla (My University, 2009)
In this study Cladocera and Copepoda (Crustacea) fauna of Seli Stream has been investigated monthly between March 2006-February 2007. In Seli Stream, 4 species of cladocerans and 2 species of copepods have been identified. All of the identified species are the first records for Seli Stream.
Keywords: Crustacea; Cladocera; Copepoda; Turkey; zooplankton; Thermocyclops; Bosmina; chlorophyll; species richness; new geographic records; geographical distribution; lakes; Elazig; zoogeography